Pseudoneutralizing test for preclinical studies of vaccines against SARS-CoV-2 - B. S. Cherepovich; A. M. Kudryashova; N. P. Kartashova; A. V. Gracheva; V. A. Manuilov; I. A. Leneva; O. V. Borisova; O. A. Svitich (Медицинская иммунология)
The purpose of this study was to evaluate efficiency of a competitive enzyme immunoassay which specifically detects antibodies that recognize the receptor-binding domain at the S1 subunit of SARS-CoV-2 coronavirus spike protein and block the formation of initiator infection complex between RBD and angiotensinconverting enzyme 2 (pseudo-neutralizing test, PNT) being applied at the stage of preclinical studies of anti- SARS-CoV-2 vaccine. We studied 37 animal blood sera (8 cows, 10 dogs) as well as 19 male and female transgenic mice of the B6.Cg-Tg(K18-ACE2)2Prlmn/HEMI line hemizygous for Tg(K18-ACE2)2Prlmn (Jackson Immunoresearch, West Grove, PA, USA)) immunized with candidate COVID-19 vaccine preparations containing SARS-CoV-2 Spike protein. In this study, 3 techniques were used for detection of antibodies to SARS-CoV-2 virus, as follows: 1) a pseudo-neutralizing test (PNT) to detect antibodies that block interaction between RBD and ACE-2; 2) neutralization test (RN) to detect virus-neutralizing antibodies, and 3) enzyme-linked immunosorbent assay to detect class G antibodies to RBD SARS-CoV-2. The results were expressed, respectively, as the suppression quotients (SC), titers of virus-neutralizing antibodies (VNA), and the positivity index (IP). The data obtained show a pronounced, statistically significant correlation between the results obtained by immunoassay methods with VNA titers determined in the studied animals by the virological neutralization test. E.g., the Spearman correlation quotients for VNA and SC titers, were, respectively, 0.9151; 0.8085, and 0.9207 for dogs, transgenic mice and cows. The Spearman quotient for VNA and PI titers was 0.8854 and 0.8955 for dogs and transgenic mice. Thus, in order to evaluate immunogenicity of vaccine preparations in our study, both methods are adequate and safe analogues to RN-ELISA for determination of IgG to RBD and PNT aoming for detection of antibodies blocking the formation of RBD/ACE-2 complex. However, the advantage of PNT is its versatility, eliminating the need to use different conjugates to detect antibodies in blood sera of different animal species. The data obtained for samples of three animal species (transgenic mice, dogs and cows) well agree with similar data obtained by us and other researchers for human blood sera, thus demonstrating high correlation between the results of PNT-like competitive tests to determine antibodies that block the formation of the RBD/ACE-2 complex, with VNA results in virologic neurtralization test (RN). Therefore, the proposed PNT technique may be used in preclinical and clinical trials of candidate vaccines and drugs.